A new species of Gerstfeldtiancylus Starobogatov, 1989 (Pulmonata: Basommatophora: Acroloxidae) from Lake Baikal - Shirokaya, Alena (Zootaxa, 2007)
Gerstfeldtiancylus ushunensis, new species (Pulmonata: Basommatophora: Acroloxidae) is described from material collected in the littoral zone of Lake Baikal. This limpet has been found only at the type locality, Malye Olkhonskie Vorota, Ushun Bay. It is distinguished from all known Baikal acroloxids by the presence of scales on the dorsal jaw part and from other representatives of Gerstfeldtiancylus by the presence of a velum in the male copulatory organ, short salivary glands and the location of the posterior shell adductor. This new species is most similar to G. roepstorfi Shirokaya et al., 2003 based on the shape of teleoconch, and most closely resembles G. renardii (Dybowski, 1884) in terms of radular morphology. Species that are morphologically identical with G. ushunensis never accompany it. G. ushunensis coexists with G. benedictiae and G. kotyensis, which are easily distinguishable from the latter.